The west wing. The complete sixth season [videorecording (DVD)] - Graves, Alex; Sheen, Martin; Spencer, John, 1946-2005; Schiff, Richard, 1955- (Warner Home Video, 2006)
Ensemble show about the inner workings of the Bartlet presidential administration.